1985
DOI: 10.3382/ps.0641148
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autoclaving and Enzyme Supplementation of Guar Meal on the Performance of Chicks and Laying Hens

Abstract: Four experiments with broilers and one with laying hens were conducted to study the effects of processing and hemicellulase supplementation of guar meal (37.0% protein) on growth, feed efficiency, and egg production. Guar meal at 0, 10, and 15%, either in raw form or autoclaved at 100, 102, or 132 C for 3, 15, or 30 min, was fed alone or in the presence of 0 to 250 ppm hemicellulase. In an experiment utilizing full-term broilers, 10 and 15% autoclaved guar meal was fed in the presence of lincomycin (3.3 ppm) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 8 publications
4
37
1
Order By: Relevance
“…Heat treatment and supple- (Patel and McGinnis, 1985;Lee et al, 2003a;2003b;2009) (Table 3). Theenzymes like pectinase in chick feed have also been recommended for overcoming growth-inhibitory properties of GM (Anderson and Warnick, 1964;Rao et al, 2015).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat treatment and supple- (Patel and McGinnis, 1985;Lee et al, 2003a;2003b;2009) (Table 3). Theenzymes like pectinase in chick feed have also been recommended for overcoming growth-inhibitory properties of GM (Anderson and Warnick, 1964;Rao et al, 2015).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…Heat treatments also have negative effects like sticky droppings; however, supplementation of enzymes can avoid such issues (Patel and McGinnis, 1985). Moreover, it is recommended to keep inclusion level of GM below 2.5% to avoid these problems (Lee et al, 2003b).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins present in guar meal also tend to form complex with protein, thus reducing the availability of protein. Most studies have reported a reduction in performance of broilers fed a diet containing GM at 25 g kg −1 or higher levels . However, it has been reported that GM can be incorporated up to 150 g kg −1 in the diets of Vanaraja, a relatively slow growing colored chicken, without affecting the performance at 42 days of age .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Hemicellulase supplementation of guar meal (37.0% protein) affects growth, feed efficiency, and egg production and hemicellulase prevented the sticky droppings. [20] The apparent viscosity of the gums was directly proportional to the gum concentration. Plant gum also contains flavonoids.…”
Section: Nutraceutical Propertiesmentioning
confidence: 99%